Exploration of Fabric Motif Design Based on Gebyok Ornamentation of Sunan Drajat’s Tomb Using Motifia - Khozinatus Sadah; Widi Sarinastiti; Akhmad Alimudin (Design Journal, 2026)
The decorative ornaments on the gebyok (wooden wall) of Sunan Drajat's tomb pavilion represent the cultural transition from Hinduism to Islam on Java's northern coast, yet studies of these ornaments remain largely confined to aesthetic and symbolic interpretation rather than applicable textile design. This study explores ornaments on two gebyok panels, CA3 and CB5, into contemporary fabric motifs using Motifia, a web-based pattern design platform from Politeknik Elektronika Negeri Surabaya, through a Research through Design approach comprising visual documentation, character analysis, ornament tracing, motif selection, and exploration. Motifs were selected based on contour clarity, representativeness of each panel's dominant character, and suitability for repetition, then composed according to modularity, repetition, symmetry, and visual balance. The exploration yielded eight distinct compositions, four from CA3 (lotus and tendril ornament) and four from CB5 (mountain, tree-of-life, and stylised lion-head ornament), with CB5-based compositions retaining the site's visual identity more strongly since their motifs are more distinctive to Sunan Drajat's tomb than the widely recurring lotus motif on CA3. The findings extend the design value of tomb ornaments beyond documentation, offering a replicable process for translating tangible heritage into applicable, culturally grounded motifs.